Unlocking Arabic Mastery: Exploring Self-Taught Language Learning with Mondly Application - Ihda Filzafatin Habibah; Titi Fitri; Renni Hasibuan (El-Syaker : Samarinda International Journal of Language Studies, 2024)
This research reveals a new and revolutionary way to learn Arabic autodidactically using the Mondly application. Despite its reputation as one of the most challenging languages in the world, this app promises to be a fun and effective way to learn. The main goal of this research is to evaluate how effective Mondly is in facilitating independent learning of Arabic and identify key factors that support user success. By analyzing real-life experiences from users, this research provides deep insight into the role of technology in changing the way we learn languages in the digital age. This research uses a qualitative descriptive approach which aims to introduce the Mondly application to the public and investigate more deeply and explain how the use of the features in it can support self-taught Arabic language learning. Data was collected through in-depth interviews and direct observation of application users. The data analysis technique used is thematic analysis, which allows researchers to identify important patterns and main themes from user experiences. The main goal of this research is to evaluate how effective Mondly is in facilitating independent learning of Arabic and identify key factors that support user success. By analyzing real-life experiences from users, this research provides deep insight into the role of technology in changing the way we learn languages in the digital age.